(untitled) (Experimental biology, 2011)
The article gives the results of the study, obtained by using complex methods of cytogenetics, mutagenesis and hybridization. Created new original forms with important breeding traits in the form of isogenic lines, mutants and recombinant forms of wheat are widely used in practical breeding